A Study on Predicting High Achievers among Medical Students in the 4th Semester Faculty of Medicine Universitas Airlangga - Hermanto Tri Joewono; Herawati, Lilik; Ummah, Fithriyah Cholifatul; Handayani, Samsriyaningsih; Chandra, Cecilia Felicia; Hasan, Helmia; Rejeki, Purwo Sri; Sakina; Heryana, Achmad Yuniari; Kuswandi, Dedi (Asian Journal of Health Research, 2025)
Introduction Student-centered learning (SCL) is based on students' needs, capacities, and other characteristics, making the method more personalized. This study aimed to analyze new questionnaires to categorize 4th-semester medical faculty students based on their characteristics. Understanding these characteristics could make the teaching and learning process more effective, potentially reducing the number of students retaking exams. Material and Methods: Subjects were 4th semester students who agreed to enroll and self-fulfilled the questionnaire. High achievers are defined as high expectations and consistent high performance (GPAs). Validity and reliability of each item were analyzed by statistical calculations accordingly. GPA in the next semester was used as threshold to confirm the participant's categorization. Results: The study commenced in March 2022, with 107 participants with Grade Point Averages (GPAs) available. The study demonstrated that the questionnaires had high validity and reliability (p-value < 0.005; Pearson Correlation Coefficient and Cronbach alpha). Among the participants, 3 (2.8%) were classified as high achievers, while 3 (28%) were categorized as low achievers. Notably, 44.86% of participants reported their passions as unrelated to medicine, while 5.61% were uncertain of their passions. Regarding vocation, 8.2% cited parental influence, and 10.3% felt their educational progress was not within their control. Conclusion: The questionnaires had high validity and reliability in item analysis. There were 2,8% of participants predicted as High Achievers and Low Achievers. Refinements of items and score presentation are needed. Follow-up activities should be given to the low achievers to prevent becoming retakers.